Indigenous Research Capability in Aotearoa - Ormond, Adreanne; Williams, Les R. Tumoana (The Australian Journal of Indigenous Education, 2013)
This article begins by considering the general nature of capability, from some dictionary meanings, then extends to theoretical perspectives related to the capability approach. As a consequence, we arrive at an operational definition that emphasises the ability to solve problems in a systematic way that brings transformation. In these terms, capability is seen as an inherent feature of the life process. The second part of this article presents a model of knowledge generation and illustrates how the development of capability is also an inherent feature of the research process in the fundamental goal of transforming both theory and practice. In the final section, we review and update the activities, initiatives and outcomes of the Capability Building program of Ngā Pae o te Māramatanga, from its beginning in late 2002 to the present, and show that this multi-level and networked program continues to be successful in building research capability. We end by listing some key objectives that are necessary for continuing to strengthen our research culture and capabilities for the future.